Proceedings of the 2nd International Conference on Healthcare Science and Engineering - Wu, Chase Q.; Chyu, Ming-Chien.; Lloret, Jaime; Li, Xianxian; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents a compilation of selected papers from the 2nd International Conference on Healthcare Science and Engineering (Healthcare 2018). The work focuses on novel computing, networking, and data analytics techniques for various issues in healthcare. The book is a valuable resource for academic researchers and practitioners working in the field.
Viral Quasispecies Spectrum Reconstruction via Coloring the Vertex in the Weighted Read Conflict Graph -- Robust feature selection method of Radiomics for grading glioma -- Cardiovascular Disease Risk Prediction based on Random Forest -- ECG Beat Classification based on Deep Bi-directional Long Short-term Memory Recurrent Neural Network -- Deep Convolutional Neural Networks for Electrocardiogram Classification -- Transfer Learning based Behavior Task Decoding from Brain Activity -- Fine-tuning ResNet for Breast Cancer Classification from Mammography -- Lung Sounds Diagnosis with Deep Convolutional Neural Network and Two-Stage Pipeline Model -- An Improved Data Anonymization Algorithm for Incomplete Medical Dataset Publishing -- ECG Classification Based on Long Short-Term Memory Networks.
Keywords: Computational intelligence; Medical informatics; Big data; Wireless communication systems; Mobile communication systems; Health services administration; Computational Intelligence; Health Informatics; Big Data; Wireless and Mobile Communication; Health Care Management